Adaptação cultural e avaliação dos parâmetros psicométricos da versão brasileira da Need for Recovery Scale - Moriguchi, Cristiane Shinohara (2009)
OBJECTIVE: To translate and culturally adapt the Need for Recovery Scale (NFR) to Brazilian Portuguese and to assess the psychometric properties of the Brazilian version among industrial workers. METHODS: The translation process followed a guideline for cultural adaptation of questionnaires, which included the stages of translation, synthesis, back-translation, committee review and pretesting. The NFR Portuguese final version (Br-NFR) was evaluated regarding reliability by tests of stability (n=52) and internal consistency (n=192); convergent validity by simultaneously assessment with other instruments: the Borg Scale (n=59); the Chalder Fatigue Questionnaire (n=57) and 3 subscales of the SF-36 (n=56). RESULTS: Stability and internal consistency achieved the criterion for a reliable measure (ICC=0.80 and Cronbach s α =0.87, respectively). The convergent validity between Br-NFR and other instruments also showed good results: Borg Scale (r=0.64); Chalder Questionnaire (r=0.67); SF-36 subscales: Vitality (r=-0.84), Physical Functioning (r=-0.54), and Role- Physical (r=-0.47). CONCLUSIONS: The Br-NFR revealed to be a reliable instrument to evaluate work-related fatigue symptoms in industrial workers. Furthermore, it showed significant and good correlations with accepted instruments in the field like the Borg Scale, the Chalder Questionnaire and SF-36 Vitality subscale, providing support for the validity of the scale.